PEMANFAATAN TEKNOLOGI GEOMATIKA DALAM SURVEI KEPENDUDUKAN RT 16 RW 02 KELURAHAN PANGERAN KOTA BANJARMASIN - Sari, Dewi Nur Indah; Sobatnu, Ferry; Inayah, Nurul; Ruhaidani, Emma (Jurnal IMPACT: Implementation and Action, 2023)
A survey is conducted to observe the situation in an area. These observations include data collection consisting of direction, distance and height in the area using certain methods (techniques). Mapping is an activity of depicting most or a small part of the earth's surface onto a flat plane, namely by taking measurements on the earth's surface which has an irregular shape. Based on the Village Law, one of the tasks carried out in the village is managing the population and managing the administration of correspondence in the village. In addition, villages also need population data to manage several government programs. Therefore, a population data survey is needed in a village. To solve this problem, RT 16 collaborated with Politeknik Negeri Banjarmasin to conduct a population data inventory. The results of the population data inventory of RT 16 and RW 02 contained 4 types of population information, namely residential houses, boarding houses and rentals, public facilities and shop houses. Keywords: Survey, Mapping, Population Data ABSTRAK Survei dilakukan adalah ntuk mengamati keadaan di suatu wilayah. Pengamatan tersebut meliputi pengumpulan data terdiri dari arah, jarak dan ketinggian pada wilayah tersebut dengan menggunakan metode (teknik) tertentu. Pemetaan merupakan kegiatan penggambaran dari sebagian besar atau sebagian kecil permukaan bumi ke atas bidang datar, yaitu dengan cara melakukan pengukuran-pengukuran di atas permukaan bumi yang mempunyai bentuk tidak beraturan. Berdasarkan UU Desa salah satu tugas yang dilakukan di desa adalah mengelola kependudukan serta pengelolaan administrasi surat menyurat di desa. Selain itu desa juga membutuhkan data kependudukan untuk mengelola beberapa program dari pemerintah. Sehingga diperlukan adanya survei data kependudukan pada suatu desa. Untuk menyelesaikan permasalahan ini, RT 16 bekerjasama dengan Politeknik Negeri Banjarmasin melakukan survei data kependudukan. Hasil dari inventarisasi data kependudukan RT 16 dan RW 02 terdapat 4 jenis informasi kependudukan yaitu rumah mukim, kost dan kontrakan, fasilitas umum dan ruko. Kata Kunci: Survei, Pemetaan, Data Kependudukan